Kinerja Return on Asset (ROA) Bank Umum Syariah dan Faktor yang Mempengaruhinya - Siti Aisyah Nurrizqi Rahmadania (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2021)
The financial performance of Islamic banks shows that bank profits are the main thing in the survival of the company. This profit performance can serve to increase capital and anticipate potential losses from disbursed financing. This research has a purpose for the performance of ROA Profitability of Islamic Commercial Banks in terms of the bank's fundamental factors that influence it. The data analysis technique used is panel data regression on 14 Islamic Commercial Banks with a data period of 2015-2019. The results of this study indicate that ROA is significantly negatively affected by BOPO and Bank Size (Total Assets) and is positively influenced by CAR.